Hegel and the infinitesimal calculus - Pissis, Jannis (Neusis, 2025)
Hegel’s Science of Logic contains a lengthy discussion of the infinitesimal calculus, that has attracted the interest of research only to a small extent. The paper attempts to place Hegel’s peculiar position within the context of the debates of his time on the foundations of the calculus, and examines in particular Hegel’s reception of Newton, Lagrange and Cauchy. Above all, the paper attempts to show that Hegel’s approach to the calculus can shed some light on key Hegelian concepts such as the concept of “true infinity” or the concept of a “moment”.